Preparation method of manganese metal organic framework material and application of manganese metal organic framework material in aqueous zinc battery

By controlling the molar ratio and dropping order of phenylatic acid and manganese acetate tetrahydrate, a uniform floral spherical manganese metal organic frame material was prepared, which solved the problems of low specific capacity and uneven morphology of the existing AZIBs electrode materials, and significantly improved the electrochemical performance.

CN119875136AActive Publication Date: 2025-04-25YANGZHOU UNIV

Patent Information

Application Number
CN202510060651.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing aqueous zinc ion battery (AZIBs) electrode materials have problems with low specific capacity and irreversible phase change, and the MnMOFs material has uneven morphology, which affects its electrochemical performance.

Method used

By controlling the molar ratio of 1: (1.5-3.2) of phenylagenic acid and manganese acetate tetrahydrate, and adding the manganese metal solution to the organic ligand solution, combining the surfactant, the raw material molar ratio and the dropping order, directional nucleation is promoted to obtain a uniform floral spherical manganese metal organic frame material.

Benefits of technology

The morphological uniformity of manganese metal organic frame material is achieved, the specific surface area is improved, and the embedding and disengagement of Zn2+ during the charging and discharging process is promoted, which significantly improves the conductivity, ion conductivity and structural stability, and has excellent specific capacity and longer cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875136A_ABST
    Figure CN119875136A_ABST
Patent Text Reader

Abstract

The invention discloses a manganese metal organic framework material preparation method, which comprises: dissolving an organic ligand trimesic acid in a solvent to form a solution A, and dissolving manganese acetate tetrahydrate and a surfactant in the solvent to form a solution B, the solvent being an aqueous solution of ethanol; slowly dropwise adding the solution B into the solution A, uniformly stirring, and standing for reaction, wherein the molar ratio of trimesic acid to manganese acetate tetrahydrate is 1: (1.5-3.2); and after the reaction is finished, cleaning a product and drying to obtain the manganese metal organic framework material. According to the application of the manganese metal organic framework material in the aqueous battery, the manganese metal organic framework material is prepared into electrode slurry, the surface of a titanium foil is coated with the electrode slurry, and the electrode slurry is dried to serve as an electrode plate of the aqueous battery. The manganese metal organic framework material with the uniform flower-ball shape is prepared, embedding and disengaging of Zn < 2 + > in the charging and discharging process are effectively promoted, and the electrochemical performance of the water-based zinc battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a metal organic framework material and application thereof, belonging to the technical field of electrode materials. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) have attracted extensive attention due to their low cost, excellent safety, high theoretical specific capacity, and low redox potential. Currently, common AZIBs electrode materials generally have problems such as low specific capacity and irreversible phase transition, which limits their competitiveness in practical applications.

[0003] MnMOFs have high working voltage and abundant active sites and are common AZIBs electrode materials. However, the MnMOFs materials obtained by existing preparation methods usually have problems such as uneven morphology and large size, which affect their electrochemical performance in AZIBs. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing a manganese metal organic framework material, the purpose of which is to control the uniformity of the material morphology and promote the 2+ Efficient embedding / de-embedding in AZIBs improves electrochemical performance. The present invention also provides an application of manganese metal organic framework materials in aqueous zinc batteries.

[0005] The technical solution of the present invention is as follows: A method for preparing a manganese metal organic framework material comprises the steps of:

[0006] The organic ligand trimesic acid is dissolved in a solvent to form a solution A, and manganese acetate tetrahydrate and a surfactant are dissolved in a solvent to form a solution B, wherein the solvent is an aqueous solution of ethanol;

[0007] Slowly drop the solution B into the solution A, stir evenly, and then stand to react, wherein the molar ratio of trimesic acid to manganese acetate tetrahydrate is 1:(1.5-3.2);

[0008] After the reaction is completed, the product is cleaned and dried to obtain a manganese metal organic framework material.

[0009] Furthermore, the surfactant is polyvinyl pyrrolidone.

[0010] Furthermore, the concentration of trimesic acid in the solution A is 12-24 mmol / L.

[0011] Furthermore, the concentration of manganese ions in the solution B is 30-40 mmol / L.

[0012] Furthermore, the volume ratio of ethanol to water in the solvent is 5:5 to 7:3.

[0013] Furthermore, the stirring speed is not less than 350 r / min, and the stirring time is 20 to 30 min.

[0014] Furthermore, the static reaction time is more than 24 hours.

[0015] Another technical solution of the present invention is as follows: an application of a manganese metal organic framework material in an aqueous zinc battery, wherein the manganese metal organic framework material obtained by the preparation method of the manganese metal organic framework material is made into an electrode slurry and coated on the surface of a titanium foil, and then used as an electrode sheet of an aqueous zinc battery after drying.

[0016] Furthermore, the electrode slurry made of the manganese metal organic framework material includes an electrode material and a slurry solvent, and the electrode material includes 70% to 75% by mass of the manganese metal organic framework material, 15% to 20% of conductive carbon black Super P, and the rest is a binder.

[0017] Compared with the prior art, the advantages of the technical solution provided by the present invention are:

[0018] The present invention controls the molar ratio of trimesic acid to manganese acetate tetrahydrate to be 1:(1.5-3.2) and drips the manganese metal solution into the organic ligand solution. This is different from the conventional method of dripping the organic ligand solution into the manganese metal solution and the molar ratio of trimesic acid to manganese acetate tetrahydrate being greater than 1. The present invention promotes the formation of directional nucleation under the combined action of a surfactant, a raw material molar ratio and a dripping sequence, effectively controls the morphology of the material, and ensures that the finally obtained manganese metal organic framework material has a uniform flower ball-like morphology.

[0019] The flower-shaped Mn-MOF material exhibits a higher specific surface area and can effectively promote the Zn 2+ The insertion and extraction during the charge and discharge process show excellent electrical conductivity, good ion conduction performance and structural stability during the charge and discharge process of aqueous zinc ion batteries (AZIBs), thus having excellent specific capacity and longer cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the X-ray powder diffraction (XRD) spectrum of the manganese metal organic framework material of Example 1.

[0021] Figure 2 This is the Fourier transform infrared (FT-IR) spectrum of the manganese metal organic framework material of Example 1.

[0022] Figure 3 This is the SEM spectrum of the manganese metal organic framework material of Example 1 (magnified 5000 times).

[0023] Figure 4 This is the SEM spectrum of the manganese metal organic framework material of Example 1 (magnified 10,000 times).

[0024] Figure 5 This is a CV curve of a battery prepared using the manganese metal organic framework material of Example 1 as the positive electrode material.

[0025] Figure 6 Cyclic stability spectrum of a battery prepared using the manganese metal organic framework material of Example 1 as the positive electrode material DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading this description, various equivalent modifications to this description by those skilled in the art fall within the scope defined by the claims attached to this application.

[0027] Example 1

[0028] (1) Weigh 25.23 mg of BTC (trimesic acid) and dissolve it in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution A.

[0029] (2) Weigh 90 mg Mn(CH 33 OO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30) were dissolved in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution B.

[0030] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 20 min.

[0031] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0032] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60 °C for 12 h to finally obtain a manganese metal organic framework material (MnBTC).

[0033] Example 2

[0034] (1) Weigh 25.23 mg of BTC (trimesic acid) and dissolve it in a mixed solution of 6 mL of ethanol and 4 mL of deionized water to obtain solution A.

[0035] (2) Weigh 90 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 6 mL of ethanol and 4 mL of deionized water to obtain solution B.

[0036] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 30 min.

[0037] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0038] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0039] Example 3

[0040] (1) Weigh 25.23 mg of BTC (trichemic acid) and dissolve it in a mixed solution of 7 mL of ethanol and 3 mL of deionized water to obtain solution A.

[0041] (2) Weigh 90 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 7 mL of ethanol and 3 mL of deionized water to obtain solution B.

[0042] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 30 min.

[0043] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0044] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0045] Example 4

[0046] (1) Weigh 33.64 mg of BTC (trimesic acid) and dissolve it in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution A.

[0047] (2) Weigh 90 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution B.

[0048] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 20 min.

[0049] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0050] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0051] Example 5

[0052] (1) Weigh 42.08 mg of BTC (trichemic acid) and dissolve it in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution A.

[0053] (2) Weigh 90 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution B.

[0054] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 20 min.

[0055] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0056] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0057] Example 6

[0058] (1) Weigh 50.46 mg of BTC (trichemic acid) and dissolve it in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution A.

[0059] (2) Weigh 90 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution B.

[0060] (3) Solution B was slowly added dropwise to solution A, with stirring speed of 400 r / min, and stirring for 20 min.

[0061] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0062] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0063] The manganese metal organic framework material prepared in Example 1 was characterized by X-ray powder diffraction (XRD) test, and the product diffraction pattern was obtained as follows: Figure 1 As shown, the diffraction peaks at 10.3°, 20.8°, 37.9°, 42.2° and 46.4° indicate the successful preparation of the flower-shaped manganese metal organic framework material, proving that the material is the expected target structure.

[0064] In addition, the functional groups of the manganese metal organic framework material prepared in Example 1 were characterized by FT-IR test. The results are as follows Figure 2 As shown, at 1574cm -1 、1437cm -1 and 762cm -1 The absorption peaks at the positions are attributed to ν(COO-), ν(C=C) and ν(Mn-O), further confirming that the manganese metal organic framework material was prepared in Example 1.

[0065] The manganese metal organic framework material prepared in Example 1 was observed by SEM. Figure 3 and Figure 4 The scanning electron microscope photos of the manganese metal organic framework material prepared in Example 1 at magnifications of 5000 and 10000 times respectively prove that the manganese metal organic framework material prepared in Example 1 has a flower ball-like morphology, and the size and shape are basically uniform. The remaining examples can also obtain manganese metal organic framework materials with flower ball-like morphology.

[0066] Comparative Example 1

[0067] (1) Weigh 50.46 mg of BTC (trichemic acid) and dissolve it in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution A.

[0068] (2) Weigh 20 mg of Mn(CH3COO)2·4H2O and 300 mg of polyvinylpyrrolidone (PVP, K30), and dissolve them in a mixed solution of 5 mL of ethanol and 5 mL of deionized water to obtain solution B.

[0069] (3) Solution A was slowly added dropwise to solution B, with stirring speed of 400 r / min, and stirring was carried out for 20 min.

[0070] (4) The mixed solution obtained in step (3) was allowed to react at room temperature for 24 hours.

[0071] (5) After washing the product three times by centrifugation with ethanol, it was dried in an oven at 60°C for 12 h to finally obtain a manganese metal organic framework material.

[0072] The manganese metal organic framework materials obtained in each embodiment and comparative example are used to assemble a battery, and the steps are as follows:

[0073] (1) Weigh 0.5 g of polyvinylidene fluoride (PVDF) and add 9.5 g of N-methylpyrrolidone (NMP), and stir for 24 h to prepare PVDF with a mass fraction of 5%.

[0074] (2) Weigh 70 mg of Mn MOF and 20 mg of Super P and grind them for 30 min.

[0075] (3) Weigh 200 mg of 5% PVDF, add it to step (2), and stir for 8 h to prepare an electrode slurry.

[0076] (4) Use a tetrahedral coater to evenly coat the electrode slurry prepared in step (3) on the surface of the titanium foil and keep it in a vacuum drying oven at 60° C. for 12 h.

[0077] (5) The electrode material prepared in step (4) was cut into electrode sheets using a 12 mm die.

[0078] (6) Prepare 2M ZnSO4·7H2O electrolyte.

[0079] (7) The electrode sheet of step (5) is used as the positive electrode, the zinc sheet is used as the negative electrode, the diaphragm is selected as a glass fiber diaphragm, the electrolyte is 2M ZnSO4·7H2O and the battery is assembled, using a gasket, a spring and a stainless steel casing. After assembly, the battery is left to stand for 24 hours to ensure good electrolyte infiltration. Further electrochemical performance tests are then carried out.

[0080] Static reaction

[0081] The assembled battery was tested for CV curve at a voltage of 0.8-1.8 V and a scan rate of 0.6 mV·s -1 . Figure 5 The test results show that the redox peak of the flower-shaped manganese metal organic framework material can be obtained from the redox potential, and the peak corresponds to Zn 2+ The embedding / ejection process.

[0082] The assembled battery was subjected to a cycle stability test with a current density of 0.3 A g -1 , cycled 150 times, and evaluated the specific capacity and cycle stability of the battery. The cycle stability spectrum of the battery prepared with the manganese metal organic framework material of Example 1 as the positive electrode material is as follows Figure 6 shown.

[0083] The results of each embodiment and comparative example are as follows

[0084]

[0085] From the above results, it can be seen that the manganese metal organic framework material prepared by the method of the present invention has a flower ball-like morphology and has better electrochemical properties than the manganese metal organic framework material prepared by the prior art.

Claims

1. A method for preparing a manganese metal organic framework material, characterized in that: Includes steps: The organic ligand trimesic acid is dissolved in a solvent to form a solution A, and manganese acetate tetrahydrate and a surfactant are dissolved in a solvent to form a solution B, wherein the solvent is an aqueous solution of ethanol; Slowly drop the solution B into the solution A, stir evenly, and then stand to react, wherein the molar ratio of trimesic acid to manganese acetate tetrahydrate is 1:(1.5-3.2); After the reaction is completed, the product is cleaned and dried to obtain a manganese metal organic framework material.

2. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The surfactant is polyvinyl pyrrolidone.

3. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The concentration of trimesic acid in the solution A is 12-24 mmol / L.

4. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The concentration of manganese ions in the solution B is 30-40 mmol / L.

5. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The volume ratio of ethanol to water in the solvent is 5:5 to 7:

3.

6. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The stirring speed is not less than 350 r / min, and the stirring time is 20 to 30 min.

7. The method for preparing a manganese metal organic framework material according to claim 1, characterized in that: The static reaction time is more than 24 hours.

8. Application of a manganese metal organic framework material in an aqueous zinc battery, characterized in that: The manganese metal organic framework material prepared by the method for preparing the manganese metal organic framework material according to any one of claims 1 to 7 is made into an electrode slurry and coated on the surface of a titanium foil, and then used as an electrode sheet of an aqueous battery after drying.

9. The use of the manganese metal organic framework material in aqueous zinc batteries according to claim 8, characterized in that: The electrode slurry made of the manganese metal organic framework material comprises an electrode material and a slurry solvent. The electrode material comprises 70% to 75% of the manganese metal organic framework material and 15% to 20% of conductive carbon black Super P in a mass ratio, and the rest is a binder.

Citation Information

Patent Citations

  • Application of chestnut-shaped graded manganese selenide / carbon composite material as lithium ion battery anode material

    CN110364702A

  • Preparation method and application of unsaturated coordination manganese-based metal organic framework composite material

    CN113444257A

  • Preparation method of manganous oxide composite material for aqueous zinc ion battery

    CN114335471A

  • Mn-based metal organic framework derived Mn2O3 / Mn3O4 heterojunction material as well as preparation method and application thereof

    CN119306256A

Cited By

  • Zinc negative electrode modified by telescopic gel interface layer as well as preparation method and application of zinc negative electrode

    CN121709515A